The antiquity of bow-and-arrow technology: evidence from Middle Stone Age layers at Sibudu Cave - Backwell, Lucinda Ruth (2018)
The bowand arrowis thought to be a unique development of our species, signalling higherlevel cognitive functioning. How this technology originated and how we identify archaeological evidence for it are subjects of ongoing debate. Recent analysis of the putative bone arrow point from Sibudu Cave in South Africa, dated to 61.7±1.5kya, has provided important new insights. High-resolution CT scanning revealed heat and impact damage in both the Sibudu point and in experimentally produced arrow points. These features suggest that the Sibudu point was first used as an arrowhead for hunting, and afterwards was deposited in a hearth. Our results support the claim that bone weapon tips were used in South African hunting long before the Eurasian Upper Palaeolithic.